TRANSFORMATION OF SOCIAL CONTROL RELATED TO THE SHIFT FROM DIRECT INTERACTION TO LAW ENFORCEMENT AUTOMATION IN THE IMPLEMENTATION OF ELECTRONIC TRAFFIC LAW ENFORCEMENT (ETLE) - Lia Christine; Achmad Benyamin Daniel; Catharina Dewi Wulansari (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
This study analyzes the legal sociology implications of the implementation of the ETLE system in Indonesia, which represents a radical shift in social control mechanisms from personal interaction to automation. The main issue that arises is the tension between the system's goal of achieving zero tolerance transparency and the social reality that creates resistance and uncertainty of accountability between vehicle owners and drivers. The urgency of this research lies in evaluating the effectiveness of ETLE in transforming traffic law enforcement, analyzing the impact of changes in social control on perceptions of justice and public trust, and examining the role of legal culture and social structure in the acceptance of the ETLE system. This research employs a normative legal method with legislative, case, and conceptual approaches. Secondary data were collected through literature review of primary legal sources such as the Traffic Law (UU LLAJ) and Police Regulation No. 2 of 2025, as well as secondary legal materials. The data were then analyzed qualitatively. The findings indicate that ETLE effectively reduces corruption and enhances certainty of enforcement at the operational level. However, the automation of social control undermines procedural justice due to ambiguities in identifying legal subjects and shifts the burden of evidence. This leads to the manifestation of entrenched negotiative legal culture as both active and passive resistance, signaling that the legal legitimacy built by technology has not been fully accepted. Therefore, the enforcement of ETLE must be complemented by structural improvements in population data and the enhancement of fair clarification channels to foster long-term normative compliance.